2019
DOI: 10.1002/14651858.cd009218.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent iron supplementation for reducing anaemia and its associated impairments in adolescent and adult menstruating women

Abstract: Intermittent iron supplementation for reducing anaemia and its associated impairments in adolescent and adult menstruating women (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 108 publications
0
35
0
4
Order By: Relevance
“…This is because exercise training can increase the total haemoglobin and red blood cells, which results in enhancing the oxygen carrying capacity of blood. Bone marrow stimulated erythropoiesis with hyperplasia of hematopoietic bone marrow and improvement of hematopoietic microenvironment are possible in underlying conditions as reported by Engy.M.et.al 8 . The need to increase oxygen during exercise can provoke hematopoietic cells to produce more oxygen carriers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is because exercise training can increase the total haemoglobin and red blood cells, which results in enhancing the oxygen carrying capacity of blood. Bone marrow stimulated erythropoiesis with hyperplasia of hematopoietic bone marrow and improvement of hematopoietic microenvironment are possible in underlying conditions as reported by Engy.M.et.al 8 . The need to increase oxygen during exercise can provoke hematopoietic cells to produce more oxygen carriers.…”
Section: Discussionmentioning
confidence: 97%
“…However, researchers have found that high dose usage of such medications is frequently associated with adverse effects such as nausea or constipation. Intermittent supplementation has been proposed as an effective and safer alternative to daily supplementation 8 . Hence, this study intended to analyse the effects of non-expensive therapies with nil side-effects for improving the haemoglobin level in females.…”
Section: Introductionmentioning
confidence: 99%
“…A 2019 systematic review revealed that intermittent iron supplementation reduced the risk of having anemia (risk ratio (RR) 0.65, 95% confidence interval (CI) 0.49-0.87) and improved the concentrations of hemoglobin (mean difference (MD) 5.19 g/L, CI 3.-07-7.32) and ferritin (MD 7.46 μg/L, CI 5.02-9.90). Women receiving iron supplements intermittently were also less likely to have less adverse side effects (RR 0.41, CI 0.21-0.82) [23]. Again, the main limitation of this study was that the review primarily targeted women and could not be generalized to men.…”
Section: Reviewmentioning
confidence: 88%
“…Una revisión sistemática de Cochrane muestra que la suplementación intermitente con hierro solo (≥60 mg de hierro elemental semanal) o en combinación con otros micronutrientes reduce significativamente la frecuencia de anemia y mejora las reservas de hierro en mujeres premenopáusicas. La evidencia de esta intervención es débil debido a la calidad de los estudios disponibles (38) .…”
Section: Materiales Y Métodosunclassified